The Behavioural Impacts of Commercial Swimming With Whale Tours on Humpback Whales (Megaptera novaeangliae) in Hervey Bay, Australia - Stack, Stephanie H.; Sprogis, Kate R.; Olson, Grace L.; Sullivan, Florence A.; Machernis, Abigail F.; Currie, Jens J. (Frontiers in Marine Science, 2021)
Swim-with-whale tourism has expanded across several countries globally, with humpback whales (Megaptera novaeangliae) being the most commonly targeted species of baleen whale. Behavioural responses from humpback whales to swim-with-whale tours have been reported, however, responses are likely context-dependent. In 2014, swimming with humpback whales began in Hervey Bay, Queensland, Australia, an important resting ground and migratory stopover for humpback whales. The behavioural responses of humpback whales to this swim-with-whale industry have not been examined in Queensland, preventing informed management of this industry. The aims of this study were to: (1) examine short-term behavioural responses in whales before, during, and after swim-with-whale tours, and (2) investigate behavioural responses of whales throughout swim-with-whale tours compared to whale watch tours. Data were collected on board a commercial vessel, where before, during and after data were collected during swim-with-whale tours (250 h) and whale watch tours (150 h). Within the swim-with-whale tours, behavioural changes were detected before, during, and after the vessel approached and placed swimmers in the water on a mermaid line, with the majority of significant changes occurring in the during and after phases. The number of direction changes made by the whales was highest when swimmers were in the water and the whales did not resume undisturbed behaviour after the swimmers exited the water. There was a 50% reduction in the proportion of time that whales spent resting during swim-tours compared to during whale watch tours. In both tour types, the time spent engaging in various behaviours was impacted by the distance between the vessel and the whale(s). These results support the conclusion that the behaviour of humpback whales in Hervey Bay was altered in response to swim-with-whale tourism. As humpback whales are capital breeders with limited energy reserves, reducing disturbance to them is of high importance for their continued population recovery and for the sustainability of the marine tourism industry. In Australia, where swim-with-whale tourism is becoming more established, robust education and enforcement programs, combined with continued monitoring of population dynamics through scientific research, are needed to minimise impacts to the population and guide adaptive management strategies.